The American financial system : markets and institutions - Ludtke, James B. (Boston : Allyn and Bacon, 1961)
In the preface to his book James B. Ludtke states that the "book is an outgrowth of considerable experience in the development of a financial institutions course, and it is designed to serve as a text in money and banking courses as well as in financial institutions courses." The book is a massive (685 pages) tome, well written, with evidences of considerable recourse to technical literature instead of mere rehashing of other texts, and thorough treatment of all the institutional aspects of the U.S. financial system. Ludtke has succeeded in writing an excellent text that should compete successfully in the market for texts in courses on financial institutions.
Includes bibliographical references and index.
rpm 02/05/2018
Loans
Keywords: Finance